Competitive Chemiluminescent Immunoassay for the Sensitive Point-of-Care Determination of Metoprolol. (11th February 2017) - Zhang, Lisha; Long, Hao; Song, Pei; Li, Xiaogang; Xu, Kun; Meng, Meng; Yin, Yongmei; Xi, Rimo
ABSTRACT: A competitive chemiluminescence immunoassay which can be used for point-of-care testing and blood screening of metoprolol is reported. Four haptens for metoprolol were synthesized. An octanedioic acid-modified hapten was conjugated with bovine serum albumin to serve as the immunogen and the haptens were conjugated with ovalbumin for the coating antigen. Polyclonal antibodies for metoprolol were produced and the detection conditions were optimized. A competitive chemiluminescence immunoassay was established based on the produced antibody with potential for bedside therapeutic monitoring of metoprolol. The limit of detection in phosphate-buffered saline was 2 ng mL −1 . Satisfactory recovery values from 89.3 to 107.6% in plasma were achieved. The results provided by the reported method were consistent with values obtained by high-performance liquid chromatography for pharmacokinetic studies. The immunoassay has potential to be developed as a test kit offering a simple and cost-effective approach for on-site monitoring of metoprolol.